Valor De La Fosfatasa Alcalina, Bilirrubina Total Y Transaminasas Como Predictores De Coledocolitiasis En Pacientes Con Coleitiasis Sintomática Atendidos En El Servicio De Cirugía General Del Hospital Belén De Trujillo. - Sebastián Lozano, Elder Raúl (2012)
Objective: Determining the diagnostic value of alkaline fosfatase (FA), total bilirubin (BT) and transamin ases (GOT and GPT) to predict choledocholithiasis in patients with symptomatic vesicular litiasic disease. Materia l and methods: we analytic study, retrospective of cases and control s, 60 medical records (20 cases and 40 controls) of patients attended and operated by choleJithiasis syrnptomatic in the service of general surgery of Belen Hospital of Trujillo during the period 2001-2011.. Was determined Odds Ratio's value with bis respective value of signi:ficancy (p), after was estimated sensibility, specificity, predictive positive value (VPP) and predicti ve negative value (VPN) of every the biochemical factors in the univariate analysis. An analysis carne true, combiníng the factors ofbigger utility in the univariate analysis calculating also sensibility, specificity, VPP and VPN. Add irionally was described variab les age, sex, signs and symptoms principals and pathological background, in measures of average, frequencies and percentages. Results: of patients total, 10 (16.7%) were mate and 50 (83.3%) female, of the patients with choledocholithiasis (20), 16 (80%) were female. The mean age of the total was 46,87± 15,7 years, in the cases the mean of age was 40,7±15,7 years and in controls 49,9±13 years. The princip al signs and symptoms in patients with choledocholithi asis: Abdominal pain with sign of Mmphy in the 20 patients (100%), jaundic e 18 (90%), nauseas and or vomits 17 (85 %), coluria 8 (40%), hiporexi a 6 (30%) and fever 4 (20%); the principal pathological background find out: HTA, diabetes mellitus and pancreatitis. In the univariate analysis of the biochemical parameters elevated : FA>480 UI L, BT>1.8 mg/dl, TG0>45 UI L and TGP>45 UI L established risk to suffer illness be associated whit coledocolitiasis, and were statistically significant (p<0.0001 ). The TGP showed a height sensibility (100%), but low specificity and VPP, the FA show a height specificity (90%) and height VPP (80%), the BT show a height VPN (94.6%). When combining the FA and TGP, obtained a height sensibility (l00%), specificity (90.3%) and VPN (100 %). Conclusions: FA, BT and TGP are good predictors for choledocholith iasis diagnosis in patients with vesicular litiasic disease. Wh en combine the biochemical parameters predictors of choledocho lithiasis, obtained better diagnostic precision.